Source Basis of Historical and Pedagogical Studies of Music Teachers in Educational Establishments in Podillia Regionin the End of the XIX – Beginning of the XX Century - Yarova, Maryna; Vovk, Valentyn (Pedagogical Discourse, 2013)
On the basis of historico-pedagogical researches of Podillia region, literary and archival sources, the concept of musical-theoretical training of music teachers in educational institutions in the end of the XIX – beginning of XX century have been traced. Specificity of educational process in educational institutions of Podillia region, which gave the opportunity to a large number of pedagogical staff to deepen their knowledge, learn new progressive methods of training, to improve conductor’s skills, to share their experience in the organization and management of the choir, get acquainted with musical literature and textbooks, has been revealed in the article.